(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Knowledge Discovery in Databases is the process of finding knowledge in massive amount of data where data mining is the core of this process. Data mining can be used to mine understandable meaningful patterns from large databases and these patterns may then be converted into knowledge. Data mining is the process of extracting the information and patterns derived by the KDD process which helps in crucial decision-making. Data mining works with data warehouse and the whole process is divided into action plan to be performed on data Selection, transformation, mining and results interpretation. In this paper, we have reviewed Knowledge Discovery perspective in Data Mining and consolidated different areas of data mining, its techniques and methods in it